Geoarchaeological investigations of Glacial Lake Agassiz and Holocene Alluvial Deposits in the Buffalo River Valley, Northwestern Minnesota - Running, Garry L.; Kuehl, Kira J.; Fedewa, Elizabeth (My University, 2017)
The Buffalo River Regional Science Center (BRRSC) is owned by Minnesota State University – Moorhead (MSU-Moorhead) and is used primarily for research purposes among several departments. The Department of Anthropology and Earth Science students and faculty are conducting a cultural resources inventory at the BRRSC (Figure 1). MSU-Moorhead faculty want to conduct the inventory efficiently and effectively. To do so, they need to identify locations in the BRRSC where in situ cultural material may be preserved. Our contribution is to identify and map historic floodplain deposits in the valley so they can be eliminated from the cultural resources inventory survey consideration.
Color poster with text, maps, images, graphs, or charts.
Keywords: Buffalo River Valley (MN); Alluvium; Geoarchaeology; Buffalo River Regional Science Center (BRRSC); Posters